2007
DOI: 10.1210/en.2006-0970
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Protects the Islets and β-Cells from Interleukin-1 β-Mediated Cytotoxicity through Negative Feedback Regulation of Nitric Oxide

Abstract: Osteopontin (OPN), a phosphorylated glycoprotein that binds to an integrin-binding motif, has been shown to regulate nitric oxide (NO) production via inhibition of induced NO synthase (iNOS) synthesis. In the transplanted islets, iNOS and toxic amounts of NO are produced as a result of islets infiltration with inflammatory cells and production of proinflammatory cytokines. Here, we demonstrate that addition of OPN before IL-1beta in freshly isolated rat islets improved their glucose stimulated insulin secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 38 publications
2
52
0
Order By: Relevance
“…Wei and colleagues (Wei et al, 2003) demonstrated that HU causes a dramatic reduction in the number of mouse splenocytes and thymocytes; the reduction in lymphocyte number resulting from stress is corticosteroid-dependent and apparently due to the induction of apoptosis. OPN has been found to inhibit apoptosis in various situations Arafat et al, 2007;Hur et al, 2007). It has previously been reported that OPN is necessary for the HU-induced remodeling of bone Yoshitake et al, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…Wei and colleagues (Wei et al, 2003) demonstrated that HU causes a dramatic reduction in the number of mouse splenocytes and thymocytes; the reduction in lymphocyte number resulting from stress is corticosteroid-dependent and apparently due to the induction of apoptosis. OPN has been found to inhibit apoptosis in various situations Arafat et al, 2007;Hur et al, 2007). It has previously been reported that OPN is necessary for the HU-induced remodeling of bone Yoshitake et al, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…Wei et al (24) demonstrated that HU caused a dramatic reduction in the number of mouse splenocytes and thymocytes; the reduction in lymphocyte number resulting from stress was corticosteroid-dependent and apparently caused by the induction of apoptosis. OPN has been found to inhibit apoptosis in various situations (1,13,14). It has previously been reported that OPN is necessary for the HU-induced remodeling of bone (1,25).…”
mentioning
confidence: 98%
“…It is classified as a T helper-1 (Th1) cytokine because it enhances production of the Th1 cytokines IFN-␥ and IL-12 and inhibits production of the T helper-2 (Th2) cytokine IL-10 (5, 6). Although it is a proinflammatory cytokine associated with autoimmune diseases, the Th1 inflammatory response, B cell function, and natural killer T cell function, it also has antiinflammatory functions, such as inhibiting the induction of inducible nitric oxide synthase and inhibiting the production of Th2 cytokines (7)(8)(9)(10)(11)(12)(13)(14). Its up-regulation is also a hallmark for many major pathological disorders, such as cardiovascular disease, cancer, and lung disease (12,15).…”
mentioning
confidence: 99%
“…Conversely, LPS in the presence of NO induced transcription of the Opn gene, suggesting a negative function of osteopontin to limit inflammatory production of NO (67). A similar negative feedback role was found for limiting NO production in rat pancreatic islets and RINm5F b cells (6).…”
Section: Roberts Et Almentioning
confidence: 55%
“…Together these findings suggest several reasons for possible resistance to Ang II-mediated vasoconstriction in arteries from Thbs1 -/-and Cd47 -/-mice, a hypothesis waiting to be tested. 6. TSP1 in aging.…”
Section: A Redox Signaling In Stem Cellsmentioning
confidence: 99%